Peranan Biro Konsultasi Pakan Ternak Dan Software Ub Feed Dalam Pemberdayaan Peternak Unggas Karangploso Malang Menuju Peternakan Organik - Muhammad Halim Natsir (Journal of Innovation and Applied Technology, 2018)
The purpose of IbiKK activities “Poultry Farmers in Karangploso Malang toward organic farming was to make poultry farm "Mr Ali" and "Mr. Tasir" into an organic farm. Results showed that 1) farmers can carry and produce their own laying hens feed formulation based so it can replace the local feed mill feed with good quality with the introduction of poultry feed formulation software (UB Feed)  and horizontal mixer, 2) breeders can create and use technology package manufacture natural feed additive antibiotics substitute a mixture of probiotics, Phytobiotic  and acidifiers, while others are still in the form of development results to be passed in the coming years, namely a) the application of organic chicken farm farming package,  b) eggs and meat products are organic rejected,  c) product marketing network both eggs and organic meat still needs to be developed. Benefits of IbiKK activity is increased farmer income because it can reduce the cost of feed which is the largest component of 70 %, farmers already have knowledge about the cultivation of laying hens to produce organic products, although not yet fully implemented due to many factors that influence and the lack of a specialized agency in Indonesia authorized to certify organic products.